Are neonatal mortality rates higher in birthing centers than in hospitals?. Issue 9 (September 2017) - Hills, Liz
Abstract : EVIDENCE‐BASED ANSWER : No. Neonatal mortality rates of freestanding and hospitalbased birth centers are not significantly different from those of hospitals (SOR: A, systematic review of RCTs and consistent cohort studies).